Coronary Microvascular Rarefaction and Myocardial Fibrosis in Heart Failure With Preserved Ejection Fraction - Mohammed, Selma F.; Hussain, Saad; Mirzoyev, Sultan A.; Edwards, William D.; Maleszewski, Joseph J.; Redfield, Margaret M. (Circulation (New York, N.Y.), 2015)
BACKGROUND—Characterization of myocardial structural changes in heart failure with preserved ejection fraction (HFpEF) has been hindered by the limited availability of human cardiac tissue. Cardiac hypertrophy, coronary artery disease (CAD), coronary microvascular rarefaction, and myocardial fibrosis may contribute to HFpEF pathophysiology. METHODS AND RESULTS—We identified HFpEF patients (n=124) and age-appropriate control subjects (noncardiac death, no heart failure diagnosis; n=104) who underwent autopsy. Heart weight and CAD severity were obtained from the autopsy reports. With the use of whole-field digital microscopy and automated analysis algorithms in full-thickness left ventricular sections, microvascular density (MVD), myocardial fibrosis, and their relationship were quantified. Subjects with HFpEF had heavier hearts (median, 538 g; 169% of age-, sex-, and body size–expected heart weight versus 335 g; 112% in controls), more severe CAD (65% with ≥1 vessel with >50% diameter stenosis in HFpEF versus 13% in controls), more left ventricular fibrosis (median % area fibrosis, 9.6 versus 7.1) and lower MVD (median 961 versus 1316 vessels/mm) than control (P<0.0001 for all). Myocardial fibrosis increased with decreasing MVD in controls (r=–0.28, P=0.004) and HFpEF (r=–0.26, P=0.004). Adjusting for MVD attenuated the group differences in fibrosis. Heart weight, fibrosis, and MVD were similar in HFpEF patients with CAD versus without CAD. CONCLUSIONS—In this study, patients with HFpEF had more cardiac hypertrophy, epicardial CAD, coronary microvascular rarefaction, and myocardial fibrosis than controls. Each of these findings may contribute to the left ventricular diastolic dysfunction and cardiac reserve function impairment characteristic of HFpEF.